Primus Lessiak and the 1920 Carinthian Plebiscite: Some Lesser-Known Biographical Details of a Linguist - Bergmann, Hubert (Jezikoslovni zapiski, 2020)
This article deals with the well-known German studies specialist Primus Lessiak (1878–1937) from Austrian Carinthia and his role before the 1920 Carinthian plebiscite. It examines his family background, ascertaining that he highly likely grew up speaking two languages: German and Slovenian. By publishing dialect propaganda poems in German and Slovenian (anonymously) before the plebiscite, he strove for Southern Carinthia to remain in Austria.